Primary squamous cell carcinoma of the seminal vesicle: A case report and review of the literature. Issue 12 (March 2019) - Fang, Lu; Hong, Qian; Chen, Lei; Wang, Yi; Bi, Liang-Kuan; Xie, Dong-Dong; Yu, De-Xin
Abstract: Rationale: Primary squamous cell carcinoma (SCC) of the seminal vesicle is extremely rare, and the clinical characteristics of this kind of malignancy are still unclear. Patient concerns: A 62-year-old male patient presented with complaints of sensation of rectal tenesmus and dysuria. Diagnosis: Ultrasonography suggested a hypoechoic mass behind the bladder, meanwhile, computerized tomography (CT) and magnetic resonance imaging (MRI) revealed a 40 mm × 45 mm × 48 mm mixed solid/cystic tumorous lesion in the right seminal vesicle. Postoperative histology confirmed the diagnosis of primary SCC in the seminal vesicle. Intervention: The mass was surgically excised with a laparoscopic approach. Postoperatively, 6 cycles of chemotherapy and 50 Gy of external beam radiation were concurrently performed on this patient. Outcomes: No local recurrence or distant metastasis was detected within 2 years after the surgery. Lessons: Primary SCC of the seminal vesicle is a rare neoplasm with a poor prognosis. Clinically, it is crucial to establish early precise diagnosis and apply multimodality treatment.